2018
DOI: 10.1038/s41598-018-32301-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of human cells exposed to an antifungal antibiotic amphotericin B reveals the mechanisms associated with the drug toxicity and cell defence

Abstract: Amphotericin B is an antibiotic used in pharmacotherapy of life-threatening mycotic infections. Unfortunately, the applicability of this antibiotic is associated with highly toxic side effects. In order to understand molecular mechanisms underlying toxicity of amphotericin B to patients, two cell lines, human normal colon epithelial cells (CCD 841 CoTr) and human colon adenocarcinoma cells (HT-29) were cultured in the presence of the drug and imaged with the application of fluorescence lifetime imaging microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Despite several decades of clinical use, AmB mechanism of action at the molecular level remains elusive and several models have been proposed based on extensive experimental research and theoretical studies [45][46][47][48]54,55,[58][59][60][61][62][63][64][65][66]. AmB has been shown to bind sterol-containing membranes of eukaryotic cells and to insert into the lipid bilayer forming pore-like supramolecular structures that can act as transmembrane ion channels, leading to increased membrane permeability, K + leakage, and disruption of ion transport [44,45,48,53].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several decades of clinical use, AmB mechanism of action at the molecular level remains elusive and several models have been proposed based on extensive experimental research and theoretical studies [45][46][47][48]54,55,[58][59][60][61][62][63][64][65][66]. AmB has been shown to bind sterol-containing membranes of eukaryotic cells and to insert into the lipid bilayer forming pore-like supramolecular structures that can act as transmembrane ion channels, leading to increased membrane permeability, K + leakage, and disruption of ion transport [44,45,48,53].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
“…On the other hand, imaging of both normal epithelial and colon adenocarcinoma human cells exposed to AmB revealed a detoxifying mechanism based on the formation of AmB-containing exosomes devoid of cholesterol, suggesting that insertion of the drug within the hydrophobic membrane core is sufficient to disturb the membrane structure and lead to cytotoxic effects [61]. The fungicidal activity of AmB has also been attributed to vacuole disintegration resulting from trafficking of the drug to the vacuolar lumen via autophagy [70].…”
Section: Amphotericin B Properties and Mode Of Actionmentioning
confidence: 99%
“…The resulting cardiomyocytes were maintained for three weeks in serum-free RPMI-1640 (R8758, Sigma-Aldrich), supplemented with B27 and Antibiotic-Antimycotic (Thermo Fisher). The final concentration of amphotericin B was 270 nM, well below the threshold concentrations reported for toxicity of this compound 76,77 . The IMR90 cardiomyocytes were reseeded at a density of 12,500 cells well −1 onto half-area 96-well plates (675096, Grenier Bio-One), coated as above, for 1 week prior to treatment.…”
Section: Methods Cell Linesmentioning
confidence: 64%
“…Therefore, this ABCA1mediated mechanism can be considered as protective against AmB cell toxicity. Recent study indicated a different defense mechanism, in which human colon cell lines minimize toxic effects of AmB by extrusion of the drug molecules from their membranes via formation of AmB-rich exosomes [60]. However, the participation of any protein in this mechanism is not documented so far.…”
Section: Discussionmentioning
confidence: 99%